Flexible School Budgeting: Funding Reform Of The Regional Schools, Case Of The Czech Republic - DANA ONDRUŠKOVÁ; RICHARD POSPÍŠIL (Global Economic Observer)
The regional school funding of public schools in the Czech Republic undergoes structural changes. The funding reform is supposed to be a part of the overall strategic policy changes in educational system. The present research analyses and compares the school budgeting formulas used for allocation the public funds for pedagogical and non-pedagogical staff of the secondary schools in the Czech Republic. By means of the selected sample of secondary schools situated in the Region of Zlín it gives a comprehensive explanation of the main differences of the previous and newly introduced allocation formula. The analysis of the budgeting formula shows the main changes and allow to compare inn order to evaluate the principles of flexible budgeting.